Management of Production System among Manufacturing Firms in Iloilo - Jaleco, Victor (JPAIR Multidisciplinary Research, 2009)
The purposes of the study were to describe the profile of the manufacturing firms, to ascertain the level of efficiency of the production system, and to describe the factors that influence the production efficiency of the manufacturing firms in the City and Province of Iloilo. The research employed the descriptive method, using the Questionnaire on the Management of Production System. The participants of the study were 187 manufacturing firms selected through random sampling method. Means, percentages, and frequency distributions were employed and Pearson r. Results showed that the majority of the manufacturers produce multiple or various types of products and employed an intermittent type of production system. The application of production strategy and specific goals and practice of production activities in managing the production system were perceived by the respondents to a “large extent”. The overall influence of internal environment factors in the management of the production system of manufacturing firms and the influence of external environmental factors were “moderate”. Manufacturing firms in Iloilo (Region VI) seemed to have a very efficient production system. The internal and external environmental factors have a “moderate” relationship, production strategy has a “moderate” relationship on the production efficiency, while the production system has a “very high” relationship on the production efficiency of manufacturing firms in Iloilo Province.
Keywords: Manufacturing firms; Production system; Production efficiency; Environmental factors; Iloilo